2015
DOI: 10.1021/acs.macromol.5b00518
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dimethylsiloxane-b-methyl methacrylate): A Promising Candidate for Sub-10 nm Patterning

Abstract: We report herein the modular synthesis and nanolithographic potential of poly­(dimethylsiloxane-block-methyl methacrylate) (PDMS-b-PMMA) with self-assembled domains approaching sub-10 nm periods. A straightforward and modular coupling strategy, optimized for low molecular weight diblocks and using copper-catalyzed azide–alkyne “click” cycloaddition, was employed to obtain a library of PDMS-b-PMMA and poly­(dimethylsiloxane-block-styrene) (PDMS-b-PS) diblock copolymers. Flory–Huggins interaction parameters, det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
135
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 50 publications
1
135
0
Order By: Relevance
“…Thus, BPs with higher‐ χ have been developed with a goal of fabricating perpendicular domains with sub‐10 nm features . One straightforward approach is to increase the incompatibility between the two polymer blocks by changing the monomers' chemical structures while maintaining the linear BP molecular architecture . For example, Gopalan and coworkers reported sub‐5 nm features (i.e., equivalent to the half of L 0 ) with higher‐ χ BPs of poly(4‐ tert ‐butylstyrene)‐ block ‐poly(2‐vinylpyridine) (PtBuSt‐P2VP) in a parallel cylinder morphology, while Ryu and coworkers used fluorine‐containing PS‐ block ‐poly‐(2,2,2‐trifluoroethyl acrylate)s (PS‐PTFEA)s to achieve 5 nm features with higher χ‐ values and demonstrated the formation of perpendicular arrays with the help of a substrate modified by a neutral homopolymer mat .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, BPs with higher‐ χ have been developed with a goal of fabricating perpendicular domains with sub‐10 nm features . One straightforward approach is to increase the incompatibility between the two polymer blocks by changing the monomers' chemical structures while maintaining the linear BP molecular architecture . For example, Gopalan and coworkers reported sub‐5 nm features (i.e., equivalent to the half of L 0 ) with higher‐ χ BPs of poly(4‐ tert ‐butylstyrene)‐ block ‐poly(2‐vinylpyridine) (PtBuSt‐P2VP) in a parallel cylinder morphology, while Ryu and coworkers used fluorine‐containing PS‐ block ‐poly‐(2,2,2‐trifluoroethyl acrylate)s (PS‐PTFEA)s to achieve 5 nm features with higher χ‐ values and demonstrated the formation of perpendicular arrays with the help of a substrate modified by a neutral homopolymer mat .…”
Section: Introductionmentioning
confidence: 99%
“…The block copolymer of butadiene with octamethylcyclotetrasiloxane (PB‐b‐PDMS) initiated by n‐butyllithium carries not only residual double bonds but also siloxane groups. In this contribution, we described here a novel strategy to prepare graft‐modified 1,2‐PB by Mo‐based coordinative polymerization of PB‐b‐PDMS and butadiene.…”
Section: Introductionmentioning
confidence: 99%
“…Microphase separation is expected to be achieved easily in P t BOS‐ b ‐P4VP diblock copolymers since a random copolymer miscibility study showed that the χ‐parameter of this combination was determined to be relatively high: 0.39 < χ 4VP, t BOS < 0.43 (even slightly higher in comparison to the PS‐ b ‐P4VP system, 0.30 < χ S,4VP ≤ 0.35). Such high χ systems are promising candidates for creating sub‐5 nm features in block copolymer systems that are otherwise impossible to achieve without additives …”
Section: Introductionmentioning
confidence: 99%